Minimizing power consumption of LoRa® and LoRaWAN for low-power wireless sensor nodes - Bäumker, Eiko; Miguel Garcia, A.; Woias, Peter (2019)
Abstract: In this paper we show that RF transmissions using the physical layer of the "Long Range" (LoRa®) interface, and with some limitations also the data link and network layer Long Range Wide Area Network (LoRaWAN), are suitable even for extremely power-restricted devices, like energy-autonomous wireless sensor nodes (WSNs), if configured well. We analyse the most critical parameters and their influence on the power performance. This includes the outer circuitry, software and configuration of the transmitter SX1276 and the new SX1262. Based on that, we give specific advice to lower their power consumption and verify the impact of these measures with evaluations on an own build low power sensor node